(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
The mung bean (Vigna radiata (L.) R. Wilczek), belonging to Leguminoseae family, is major short-seasoned legume grown in tropical and subtropical regions, mainly during the Kharif and summer seasons. Present investigation aimed to check the effects of different extraction techniques and solvents on FTIR spectrophotometric analysis and quantitative profiling of phenols and flavonoids, followed by an assessment of the antioxidant and antimicrobial activity of mung bean seeds. Methanolic extracts of seeds obtained through Soxhlet extraction, maceration and ultrasonication were subjected to solvent-aided fractionation using the separation funnel method. The extractive yield of obtained fractions ranged from 2.86 to 59.85%. The results indicated maximum yield in aqueous fractions, followed by butanol and hexane fractions, while the lowest in ethyl acetate and chloroform fractions. The phenolic content, flavonoid content and FRAP values in the different fractions varied from 16.32±1.67 to 56.82±0.88 mg of GAE/g, 38.21±0.07 to 149.95±0.53 mg QE/g, and 41.54±0.56 to 104.81±0.48 mg Fe (II) E/g, respectively. Phenolics were higher in non-polar fractions, while flavonoids and FRAP values were higher in polar fractions. Pearson correlation displayed a strong correlation between TFC and FRAP assay. The antimicrobial activity revealed Staphylococcus aureus as the most susceptible, followed by Bacillus subtilis and Saccharomyces cerevisiae; conversely, Pseudomonas sp. was shown to be most resistant with no inhibition activity. Overall, ethyl acetate fractions from all the extraction techniques presented the best results against tested microbial samples. PCA analysis presented significant discrimination among solvents and extraction techniques. Mung beans can be used as nutraceuticals pharmaceuticals and functional foods.